Production and quality of lettuce seed as a function of seedling age - Toledo Rodrigues Claudio, Marina De; Da Cunha Salata, Ariane [UNESP]; Oliveira Magro, Felipe; Ismael Inácio Cardoso, Antonio [UNESP]; Gomes Nakada-Freitas, Pâmela [UNESP] (Taylor & Francis, 2020)
Age of lettuce (Lactuca sativa L.) seedlings can affect plant development after transplanting where older seedlings can delay development of plants after transplanting and lengthen the crop cycle. For seed production, when the cycle is longer, it is not known if this effect continues until full maturity. The experiment was undertaken to determine the effects of seedling age on production and quality of lettuce, cv. Verônica, seed. Seedlings aged 28, 33, 38, 43 or 48 days after sowing were established in a plastic-covered high tunnel. At transplanting, number of leaves, fresh and dry weight were evaluated, and at the end of cycle, fruit maturity production and quality (germination and vigor) of seeds were evaluated. The older the seedlings, the greater the number of leaves and plant fresh and dry weights. Seedling age did not influence seed production (avg. 27.1 g and 25,291 seeds per plant) and quality (germination and emergence 84% and 92%, respectively) of lettuce seed. Based on results producers can choose the seedling age that most fits with their comfort levels and economic expenditure.
Keywords: germination; Lactuca sativa; tray; vigor